2010
DOI: 10.1007/s11999-010-1308-6
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Knee Arthroplasty Infection: Incidence and Predictors

Abstract: Background Deep infection remains one of the most devastating and costly complications after total knee arthroplasty (TKA). The risk of deep infection after revision TKA is reportedly greater than that for primary TKA; however, we do not know the exact incidence of infection after revision TKA. Questions/purposes We determined the incidence of infection after revision, the type of microorganisms involved and TKA, and the potential risk factors for this infection. Methods We retrospectively reviewed 475 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
132
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(158 citation statements)
references
References 35 publications
11
132
0
5
Order By: Relevance
“…Infections are the main cause of failure after prosthetic revision as revealed by recent studies with a risk that may be 10-fold higher than primary procedures [54,55]. We recommend the use of synthetic materials to reinforce the apparatus, when a direct repair is not possible.…”
Section: Discussionmentioning
confidence: 91%
“…Infections are the main cause of failure after prosthetic revision as revealed by recent studies with a risk that may be 10-fold higher than primary procedures [54,55]. We recommend the use of synthetic materials to reinforce the apparatus, when a direct repair is not possible.…”
Section: Discussionmentioning
confidence: 91%
“…Tempo cirúrgico prolongado (superior a 150 minutos), transfusão sanguínea e realização de artroplastia bilateral em um mesmo tempo cirúrgico são outros fatores relacionados a maior ocorrência de infecção. Qualquer fator que retarde a cicatrização da ferida cirúrgica como necrose isquêmica, hematoma, celulite ou abscesso de ferida, aumenta o risco de infecção, uma vez que os tecidos profundos contíguos à prótese estão desprovidos das barreiras locais de defesa (1,2,4) . É importante salientar que a presença da prótese articular leva a um prejuízo da função dos granulócitos locais, que se acumulam ao redor do implante e são parcialmente degranulados, com diminuição na produção de superóxido desmutase e prejuízo na capacidade de defesa contra bactérias, particularmente contra Staphylococcus aureus.…”
Section: Fatores De Risco E Fisiopatogeniaunclassified
“…O sucesso do tratamento das infecções das próteses articulares depende do extenso desbridamento cirúrgico e da antibioticoterapia adequada e efetiva (2,4) . Os quadros infecciosos que se desenvolvem no primeiro ano de pós-operatório são considerados infecções hospitalares e devem ser tratados até os resultados das culturas colhidas em centro cirúrgico com antibióticos que tenham ação na microbiota hospitalar do serviço onde foi realizada a cirurgia.…”
Section: Tratamentounclassified
See 1 more Smart Citation
“…Murray et al [6] reported that when a patient presents with periprosthetic joint infection (PJI) at a single site, there is an approximately 15% risk of PJI in a second site of a preexisting prosthetic joint [4]. This risk of PJI in a preexisting site is much greater than the infection risk in primary THA and TKA commonly reported to be approximately 1% [5,7].…”
Section: Introductionmentioning
confidence: 99%